A Model of Income Insurance and Social Norms - Assar Lindbeck; Mats Persson (Research Institute of Industrial Economics (IFN), 2006)
A large literature on ex ante moral hazard in income insurance emphasizes that the individual can affect the probability of an income loss by choice of lifestyle and hence, the degree of risk-taking. The much smaller literature on moral hazard ex post mainly analyzes how a moral hazard constraint can make the individual abstain from fraud (mimicking). The present paper instead presents a model of moral hazard ex post without a moral hazard constraint; the individual's ability and willingness to work is represented by a continuous stochastic variable in the utility function, and the extent of moral hazard depends on the generosity of the insurance system. Our model is also well suited for analyzing social norms concerning work and benefit dependency.
Keywords: G22; H53; I38; J21; 330; Moral Hazard; Sick Pay Insurance; Labor Supply; Asymmetric Information; Moral Hazard; Gesetzliche Krankenversicherung; Arbeitsangebot; Asymmetrische Information; Soziale Norm